Ideology deconstruction of Islamic State of Iraq and Syria (ISIS) returnees in Indonesia - Didik Novi Rahmanto; Adrianus Eliasta Meliala; Ferdinand Andi Lolo (IAIN Salatiga, 2020)
This paper discusses the problem of the Islamic State of Iraq and Syria (ISIS) foreign terrorist fighters who return to Indonesia, or called returnees. The establishment of ISIS in Syria and its propaganda related to the Khilafah attracted many Muslims in the world to emigrate, jihad, and settle in Syria. After the defeat suffered by ISIS in various regions in Syria, finally many of these foreign terrorist fighters returned to their respective countries of origin. So far, there has been a lot of literature and research that explains the potential threats related to the return of foreign terrorist fighters to their home countries. However, by studying Indonesian returnees, this research found that returnees returned and decided not to be part of a terrorist group network in Indonesia anymore. This change of understanding becomes interesting to be analysed further so that things get changed in their understanding so that they no longer want to be affiliated with ISIS or terrorist groups who are committed to ISIS. This research is basic research that aims to explore new issues. Changes in the understanding of Muslim groups that initially supported ISIS can change. This phenomenon examined using Just World Theory and Deconstruction to find out what factors influence the change in understanding. The results found several factors such as family, feeling uncomfortable, the cruelty of ISIS, experiencing sexual violence, expectations, and teachings in the Quran and Hadits.